Review of Numerical Simulation Research on Submersible Mixer for Sewage - Fei, Tian; Erfeng, Zhang; Chen, Yang; Weidong, Shi; Chenghua, Zhang (Frontiers in Energy Research, 2022)
Submersible mixer is the core machinery of sewage treatment, which has a profound effect on the efficiency and performance of submersible mixing system of sewage treatment. This paper summarizes the scientific research results of submersible mixer in recent years from four aspects: structure and energy characteristics of submersible mixer, numerical simulation calculation method, flow field characteristics and factors affecting the flow field characteristics. The existing published literature indicates that the structure of submersible mixer for sewage is complicated and the parameters of energy characteristics are special. Few experimental studies are conducted, and mostly numerical calculations are based on clear water as the medium; Mixture model based on Euler-Euler method is the multiphase flow model that is currently applied in the field of submersible mixer research. There are many factors affecting the mixing effect of submersible mixer, such as installation factors as the location and angle of installation and impeller design parameters such as blade gap, hub-tip ratio, blade angle, etc. all have a significant impact on the mixing performance. Meanwhile, the development and trends of submersible mixer technology are prospected, and the future directions of further research are proposed: establishing a more suitable numerical calculation method for submersible mixer based on the Euler-Lagrange model; construct the calculation model with real fluid——solid-liquid two-phase flow as the medium, explore the influence of various parameters on flow field characteristics of mixing fluid, get the mixing mechanism of submersible mixer, promote the development of submersible mixer, and realize efficient and stable operation of submerged mixing system.